2017
DOI: 10.3390/bioengineering4020038
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of CHO Cells for the Production of Recombinant Glycoprotein Vaccines with Xylosylated N-glycans

Abstract: Xylose is a general component of O-glycans in mammals. Core-xylosylation of N-glycans is only found in plants and helminth. Consequently, xylosylated N-glycans cause immunological response in humans. We have used the F-protein of the human respiratory syncytial virus (RSV), one of the main causes of respiratory tract infection in infants and elderly, as a model protein for vaccination. The RSV-F protein was expressed in CHO-DG44 cells, which were further modified by co-expression of β1,2-xylosyltransferase fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…However, other studies have reported that soybean glycoprotein contained a high-mannose-type N -glycan proportion (76%), while the complex type N -glycans were lower (24%) . Additionally, the storage glycoprotein N -glycan MMXF3 derived from Ginkgo seeds has been shown to continuously increase during the entire period of seed development; however, high-mannose-type N -glycan content was most abundant in the mature seed. ,, Furthermore, research using glycoengineered cells showed that the RSV-F glycoprotein containing xylosylated N -glycans displayed stronger immunogenicity than non-xylosylated N -glycans . We used the NaOH-PMP method developed by our lab to release the O -glycan of the yam glycoprotein 30CYGP .…”
Section: Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, other studies have reported that soybean glycoprotein contained a high-mannose-type N -glycan proportion (76%), while the complex type N -glycans were lower (24%) . Additionally, the storage glycoprotein N -glycan MMXF3 derived from Ginkgo seeds has been shown to continuously increase during the entire period of seed development; however, high-mannose-type N -glycan content was most abundant in the mature seed. ,, Furthermore, research using glycoengineered cells showed that the RSV-F glycoprotein containing xylosylated N -glycans displayed stronger immunogenicity than non-xylosylated N -glycans . We used the NaOH-PMP method developed by our lab to release the O -glycan of the yam glycoprotein 30CYGP .…”
Section: Results and Discussionmentioning
confidence: 98%
“…21,32,33 Furthermore, research using glycoengineered cells showed that the RSV-F glycoprotein containing xylosylated N-glycans displayed stronger immunogenicity than non-xylosylated N-glycans. 34 We used the NaOH-PMP method developed by our lab to release the O-glycan of the yam glycoprotein 30CYGP. 35 As a result, Oglycan was not detected via mass spectrometry but contained a special form of N-glycan modified only by xylose and fucose that may be related to the observed biological activity.…”
Section: Journal Of Proteome Researchmentioning
confidence: 99%
“…Cells for expression of soluble RSV-F were obtained according to Sandig et al [ 5 ]. In brief, a cDNA was constructed containing the N-terminal extracellular part of RSV-F, an N-terminal Mellitin signal sequence, and a C-terminal Factor Xa cleavage site fused with a 6xHis-tag.…”
Section: Methodsmentioning
confidence: 99%
“…However, glycans with and without fucose are both common in humans and, therefore, a direct adjuvant role is highly unlikely. This is in contrast to monosaccharides artificial to humans, e.g., N-glycan-bound xylose, which may work as adjuvants [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of cell line engineering are however not limited to antibody production only, but have also been explored in production of other biopharmaceutical products such as other recombinant proteins, vaccines, fusion proteins, growth factors etc. ( Xiao et al, 2014 ; Genzel, 2015 ; Johari et al, 2015 ; Sandig et al, 2017 ). Cell engineering approaches have also been used to obtain a desired attribute or quality in the target product produced by a cell, reduce those host cell proteins which could act as impurity and adversely impact the final product during downstream processing, or identify of an optimal site in host cell genome in order to target a transgene to that location ( Gadgil, 2017 ).…”
Section: Cell Engineering Toward Production Of Novel Antibodies For Tmentioning
confidence: 99%